Persepsi Mahasiswa pada Pelaksanaan Program Kampus Mengajar di Universitas Islam Riau - Fatikhah, Nur; Amalia, Rizka; Muhayatun, Siti; Mukhlis, Muhammad (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
Seeing the number of enthusiasts in the teaching campus program that is followed by students. So, researchers feel interested in examining the impact or influence of the campus teaching program through students who have participated in the program. So the title of this study is "The Influence of Teaching Campus Programs Through Student Perceptions at Riau Islamic University." Data collection techniques in this study used a questionnaire (questionnaire). The data analysis technique starts with data collection which is then analyzed descriptively. The data source is students of the Indonesian Language and Literature Education study program who have participated in the teaching campus program. The result of this analysis is that as many as 100% of the participants feel that they have personally had a positive impact from teaching campuses. In terms of difficulty adapting at the referral school, 50% of participants answered no, but 40% might and 10% experienced difficulties. As many as 80% of participants thought that teaching campuses had a good influence on academic careers